2019
DOI: 10.3168/jds.2018-15401
|View full text |Cite
|
Sign up to set email alerts
|

Calf care personnel on dairy farms and their educational opportunities

Abstract: As dairy herd sizes become larger and the organization of the business more complex, targeting communication and education to enhance animal care becomes more difficult. The purpose of this study was to describe selected demographics of calf care employees on large (>500 animals) and small (<501 animals) dairy farms that raise their own calves. Two to 8 individuals per farm involved with calf care, including owners, veterinarians, and calf managers, feeders, and treaters, were interviewed in either English or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
1
10
2
1
Order By: Relevance
“…A second explanation is that on some farms we may have failed to teach employees how to use clinical criteria to support treatment decisions. In previous work, we have shown that veterinarians have infrequently been involved in calf-care worker training and that most training occurs within the farm workforce, either worker-to-worker or manager-to-worker (Sischo et al, 2019). Either way, if treatment protocols include clear definitions of disease, particularly for diarrhea, calf-care workers might be better able to target appropriate interventions and reduce antimicrobial use.…”
Section: Discussionmentioning
confidence: 99%
“…A second explanation is that on some farms we may have failed to teach employees how to use clinical criteria to support treatment decisions. In previous work, we have shown that veterinarians have infrequently been involved in calf-care worker training and that most training occurs within the farm workforce, either worker-to-worker or manager-to-worker (Sischo et al, 2019). Either way, if treatment protocols include clear definitions of disease, particularly for diarrhea, calf-care workers might be better able to target appropriate interventions and reduce antimicrobial use.…”
Section: Discussionmentioning
confidence: 99%
“…Standard operating procedures (SOP) are a set of steps that show how a process should be performed (Gough and Hamrell, 2009). When implemented, SOP have the ability to harmonize practices among workers and can be used to train new or existing employees (Barbe et al, 2016;Sischo et al, 2019). With increases in farm size and the use of non-family labor (Barkema et al, 2015), and a move toward increased use of technology (Hagevoort et al, 2013), SOP are likely to be increasingly important on dairy farms.…”
Section: Introductionmentioning
confidence: 99%
“…Deming et al (2019) reported that participation in a dairy farm management program increased managerial skills in financial and personnel resources, leadership, communication, and decision-making on the farm. In a sample of US calf care personnel, 70% of owners reported that they had attended college, compared with only 37% of calf managers (Sischo et al, 2019). Only 13% of dairy farm employees from 4 US states reported having some form of higher education (Rodriguez et al, 2018).…”
Section: Professional Development and Educationmentioning
confidence: 99%
“…The US dairy industry is highly dependent on foreign labor (Jenkins et al, 2009), with many workers having little dairy experience (Hagevoort et al, 2013). In a survey of calf care personnel in the United States, Sischo et al (2019) found that as the number of calves reared increased, the proportion of calf care employees who were comfortable speaking English decreased. Dual language training resources have been cited as important for farm practices such as antibiotic use (Friedman et al, 2007).…”
Section: Training and Languagementioning
confidence: 99%
See 1 more Smart Citation